An Analysis of Cohesive Devices on Phoenix Posts on The Death of Queen Elisabeth II - Peniel Zaazra Nouhou; Ngonjo Victor Fuh (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
This paper explores some cohesive devices namely reference, repetition, and collocation on Phoenix messages by internet users worldwide in reaction to the death of Queen Elizabeth II of the United Kingdom. 400 e-messages on Phoenix platform were collected from 175 informants. Each participant provided at most three e-messages. The study examines the types of cohesive devices and the extent to which they are used in the various conversations of the texters. Insights were drawn from Halliday and Hassan (1976) who laid down the foundation of cohesion theory in English. They identified two different types of cohesive devices namely grammatical and lexical cohesion. The grammatical type is made up of reference, conjunction, substitution, and ellipsis; while lexical one comprises reiteration and collocation. Facts from the analysis of the data revealed that reference was the dominant cohesive devices. More precisely, the demonstrative pronouns (28.57%) are the most used referential items. it is seconded by possessive pronouns (23.42%) and the least employed devices is personal pronouns (20.57%). The results also indicated the use of repetition and collocation in messages of the participants. The most repeated word is Queen while the least reduplicated one is slave/slavery. Items of collocation are used at varying frequencies.